How Important is Secondary School Duration for Post-school Education Decisions? Evidence from a Natural Experiment - Tobias Meyer; Stephan L. Thomsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2012)
This paper investigates how post-school education decisions are affected by a one-year reduction of secondary school duration with an unchanged curriculum. Until recently, Germany had had a longstanding tradition of 13 years of schooling in preparation for university. During the last decade, however, most states abolished the 13th year. The implementation of the reform in 2003 in the state of Saxony-Anhalt provides a natural experiment for identification. Based on data from the double cohort of graduates, our estimates show significant effects of the reform. Affected female students in particular significantly delay university enrollment by one year, show a slightly lower participation in university education overall and are more likely to start a vocational education course. We can also reveal effect heterogeneity with respect to the fields of study. Due to the reform the probability of affected males studying mathematics or natural sciences is significantly reduced.
Keywords: I21; J18; C21; 330; school duration; learning intensity; education decision; natural experiment; Germany